Environment is associated with chytrid infection and skin microbiome richness on an amphibian rich island (Taiwan) - Dirk S. Schmeller; Tina Cheng; Jennifer Shelton; Chun-Fu Lin; Alan Chan-Alvarado; Adriana Bernardo-Cravo; Luca Zoccarato; Tzung-Su Ding; Yu-Pin Lin; Andrea Swei; Matthew C. Fisher; Vance T. Vredenburg; et al. (Scientific Reports, 2022)
Abstract Growing evidence suggests that the origins of the panzootic amphibian pathogens Batrachochytrium dendrobatidis (Bd) and Batrachochytrium salamandrivorans (Bsal) are in Asia. In Taiwan, an island hotspot of high amphibian diversity, no amphibian mass mortality events linked to Bd or Bsal have been reported. We conducted a multi-year study across this subtropical island, sampling 2517 individuals from 30 species at 34 field sites, between 2010 and 2017, and including 171 museum samples collected between 1981 and 2009. We analyzed the skin microbiome of 153 samples (6 species) from 2017 in order to assess any association between the amphibian skin microbiome and the probability of infection amongst different host species. We did not detect Bsal in our samples, but found widespread infection by Bd across central and northern Taiwan, both taxonomically and spatially. Museum samples show that Bd has been present in Taiwan since at least 1990. Host species, geography (elevation), climatic conditions and microbial richness were all associated with the prevalence of infection. Host life-history traits, skin microbiome composition and phylogeny were associated with lower prevalence of infection for high altitude species. Overall, we observed low prevalence and burden of infection in host populations, suggesting that Bd is enzootic in Taiwan where it causes subclinical infections. While amphibian species in Taiwan are currently threatened by habitat loss, our study indicates that Bd is in an endemic equilibrium with the populations and species we investigated. However, ongoing surveillance of the infection is warranted, as changing environmental conditions may disturb the currently stable equilibrium.